A data-hiding technique using scene-change detection for video steganography. (August 2016) - Ramalingam, Mritha; Isa, Nor Ashidi Mat
Highlights: Enhances the security of embedded message by using scene-change detection and discrete cosine transforms of video sequences. Reduces distortions. Enhances video quality using discrete wavelet transforms in video sequences. Abstract: This paper presents a data-hiding technique using scene-change detection for video steganography. Reducing the distortions in videos and securing the embedded data remain as competing goals in any video steganographic system. In this study, a data-hiding technique using discrete cosine transform (DCT) and discrete wavelet transform (DWT) coefficients is proposed to enhance the security of hidden data and minimize distortions to maintain better video quality. In this work, scene changes are detected using the DCT coefficients of video sequences for hiding data. Then, the cover-video and the payload are fused and normalized using the DWT coefficients to enhance video quality. The MATLAB simulation results indicate that the proposed method outperforms existing state-of-the-art methods. The comparison results reveal that the proposed data-hiding method offers better security and minimizes distortions for better video quality. Graphical abstract: